Marketing Segmentation and Increasing Sales Volume in an Islamic Economic Perspective - Widodo Saputro, Wahyu; Mustofa (Journal of Islamicate Studies, 2023)
Market segmentation is a fundamental strategy in understanding diverse customer needs and preferences. This research uses a qualitative method with a literature study approach. Results from previous research and business practice confirm that market segmentation has a significant positive impact on a company's sales volume. First, segmentation allows companies to have a deep understanding of the characteristics, needs, and preferences of customers within each segment, leading to the development of more appropriate products, services, and marketing messages. Second, through personalization of marketing messages and actions, segmentation increases the relevance of communications to customers, increasing interest and the likelihood of purchase. Furthermore, marketing segmentation helps companies to more efficiently allocate marketing resources, avoid waste, and direct efforts to the most relevant customer segments. Responsiveness to market changes is enhanced, allowing companies to quickly adapt their marketing strategies in the face of market changes. Overall, market segmentation is a crucial strategic tool in achieving increased sales volumes in a competitive business environment. This helps companies better respond to customer needs, optimize the use of resources, and create stronger relationships with customers, all factors that contribute to significant sales growth.